Q: What is the factor of 27x squared y squared - 36xy?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

it is (x-y)(x-y) :)

15

(y + 8)(y - 7)

(a + x^2)(b + y^2)

(3x - y+ 2)(3x + y + 2)

Related questions

it is (x-y)(x-y) :)

35

15

15

The factoring is as follows: x2 - y2 = (x + y) * (x - y)

(y + 8)(y - 7)

(a + x^2)(b + y^2)

(3x - y+ 2)(3x + y + 2)

C2x + C2y = C2(x + y)

X + Y (X + Y) ^2 = (X+Y)(X+Y) Factor = (X + Y)

x(y - 1)(y + 1)

All you can do to factor that expression is to divide both terms by y: y2 + 4y = y(y + 4)